2019
DOI: 10.3390/ijerph16030465
|View full text |Cite
|
Sign up to set email alerts
|

Decisions of the Dual-Channel Supply Chain under Double Policy Considering Remanufacturing

Abstract: Considering the preference of green consumers for remanufactured products, a dual-sale-channel supply chain model with government non-intervention, government remanufacturing subsidy policy, and carbon tax policy is constructed, respectively. The difference of the optimal decision between the firm and the government under the two policies is discussed in this paper. Meanwhile, we analyze the influence of green consumers on the government’s optimal decision, based on social welfare maximization. It is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The goal of innovation cooperation is difficult to achieve, which shows that the policy instruments for GBT innovation cooperation are legitimate and reasonable. The findings of this study are generally consistent with previous studies [42]. Government intervention reduces the cost of technological innovation cooperation for green building enterprises, enhances the efficiency of resource allocation, and overcomes the market failure of GBT innovation.…”
Section: Conclusion and Contributionssupporting
confidence: 91%
“…The goal of innovation cooperation is difficult to achieve, which shows that the policy instruments for GBT innovation cooperation are legitimate and reasonable. The findings of this study are generally consistent with previous studies [42]. Government intervention reduces the cost of technological innovation cooperation for green building enterprises, enhances the efficiency of resource allocation, and overcomes the market failure of GBT innovation.…”
Section: Conclusion and Contributionssupporting
confidence: 91%
“…Subsidy policies from local governments are also a crucial driving force for CEEs to implement strategies for carbon emission reduction [ 40 ]. In addition, carbon tax policies, especially bilateral dynamic taxes, are an effective means to control the carbon emissions of CEEs [ 41 , 42 ]. However, carbon emission reduction has increased CEEs’ production costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modak et al concluded that the optimal recycling rate increases with the CSR activity of the manufacturer, and a profit-sharing contract provides the best channel performance in a closedloop distribution channel consisting of a socially responsible manufacturer, multiple retailers, and a third-party collector [54]. Feng infers that win-win results can be achieved by establishing profit-sharing contracts considering the preference of green consumers [55]. Previous papers often focus on two aspects, including the choice of contract and the conditions of the contract.…”
Section: Cooperationmentioning
confidence: 99%